Measuring response human capital to investment in elements - السعيدي يعرب عدنان; معارج هديل سعدون (Journal of Economics and Administrative Sciences, 2017)
This aim research of this discussion impact of investment in human capital dimensions (training, education, knowledge management, skills development) and its components (knowledge, skills, abilities, value) with the Office of the Inspector General’s staff - Ministry of Culture in Iraq, has depended questionnaire as a tool in the collection data and information ,subjected to a measure of validity and reliability, and distributed to a sample of (63) individuals were distributed in positions (director, director of the Division of employees) have been analyzed data search using ready-statistical software (SPSS) the used hypothesis testing and correlation coefficient) Spearman (and regression analysis. the statistical methods have produced a number of conclusions, most notably the existence of differences in point of managers and employees significent human capital investment,.diffrent in orrentation management in human capital investment the back of investment in capital human accepted and achieved a good position in the long term. In the light of the conclusions Search recommended the need to develop an integrated strategy and signific invest in human capital general direction of investment of is in decline, which will reflect. Negatively on human capital the importance of investing in human capital because it contributes to strengthen and improve and develop the performance of the Office of the Inspector general because The attention to training activity and deeper down to see how much real value added through advanced training programs to benefit from the expertise of academics and consultants.